2016
DOI: 10.1016/j.electacta.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Sulfidizing Resistance of High Reflective Multilayered Sn/Ag3Sn and Sn/Ag Films Electrodeposited on Cu Alloy Sheets

Abstract: We reported multilayered Sn/Ag 3 Sn and Sn/Ag films with Ag thickness of 20-300 nm that electroplated on a reflowed Sn layer on Cu alloy sheets as promising coating materials for LED lead-frames. The morphology, surface roughness, crystalline structure, and reflectance of multilayered Sn/Ag-based films are more dependent on plating baths than on Ag thickness. The Sn/Ag 3 Sn film obtained from a cyanide Ag bath exhibited high specular reflectivity of 65-70% (480 nm), whereas the Sn/Ag films from a cyanide-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…15,16 The 2nd approach that used to simplify co-deposition is the reduction of the potential gap between the two constituents utilizing additives such as methionine. 17 Therefore, the inclusion of methionine can facilitate the (Sn, Ag) co-deposition by reducing the potential gap between the reduction peak of silver and reduction peak of tin. These ndings agree well with the results of Low and Walsh for the deposition of Cu-Sn alloys utilizing other additives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The 2nd approach that used to simplify co-deposition is the reduction of the potential gap between the two constituents utilizing additives such as methionine. 17 Therefore, the inclusion of methionine can facilitate the (Sn, Ag) co-deposition by reducing the potential gap between the reduction peak of silver and reduction peak of tin. These ndings agree well with the results of Low and Walsh for the deposition of Cu-Sn alloys utilizing other additives.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that most of Ag ions are incorporated into the alloys. 17,25 The average crystallite size of the alloy is calculated using values of full width at half maximum (W) for the main three Ag/Sn peaks through Scherrer's equation; D s ¼ 0.94l/W cos q; in which q and l are the Bragg's angle and X-ray wavelength. 26,27 Also, the texture coefficients (TCs) and dislocation densities are calculated.…”
Section: Resultsmentioning
confidence: 99%
“…To solve the problem, various techniques, including use of capping layers overlayers [811] and Ag alloys [1215], have been introduced. For instance, the thermal stability of Sn-capped Ag films was investigated as a function of Ag thickness (varying from 20 to 300 nm) [11]. It was found that the surface roughness and reflectance of Sn/Ag films were dependent on plating baths and the Sn/Ag films showed a reflectivity of 94% similar to commercial Ag films.…”
Section: Introductionmentioning
confidence: 99%